2010
DOI: 10.1186/1471-2296-11-33
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Herpes Zoster Infection among Patients Treated in Primary Care Centres in the Valencian Community (Spain)

Abstract: BackgroundThere is little available data regarding the epidemiology of herpes zoster (HZ) in Spain. This study's main goal was to estimate the annual incidence of HZ in the Autonomous Community of Valencia.MethodsFrom December 1st 2006 to December 1st 2007, a prospective study was carried out in 24 primary health care centres that together provide care for a population of 36,030 persons aged >14 years. We included all adult patients with a clinical diagnosis of HZ who were seen at these centres during the one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 33 publications
0
27
1
6
Order By: Relevance
“…A recent study has shown no significant differences in the incidence of HZ between European countries. 24 In addition, studies in Spain (Navarre, 19 Valencia, [14][15][16] and Madrid 18 ) based on administrative data from primary healthcare show very similar results (overall incidence in all age groups of about 4 per 1000 inhabitants, although the Valencian study 14,15 did not include subjects aged <14 y). The study by Yawn et al, 7 one of the most comprehensive epidemiological studies of HZ, found similar incidence rates to those observed in Spain, as did other studies performed in Europe, [25][26][27][28][29] Israel, 30 and the United States.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A recent study has shown no significant differences in the incidence of HZ between European countries. 24 In addition, studies in Spain (Navarre, 19 Valencia, [14][15][16] and Madrid 18 ) based on administrative data from primary healthcare show very similar results (overall incidence in all age groups of about 4 per 1000 inhabitants, although the Valencian study 14,15 did not include subjects aged <14 y). The study by Yawn et al, 7 one of the most comprehensive epidemiological studies of HZ, found similar incidence rates to those observed in Spain, as did other studies performed in Europe, [25][26][27][28][29] Israel, 30 and the United States.…”
Section: Discussionmentioning
confidence: 87%
“…In Spain, incidence studies of HZ have been published based on data obtained from public primary healthcare centers in Valencia, [14][15][16] Madrid 17,18 and Navarre. 19 In Navarre, which has an excellent public health system, the proportion of patients seen by private family physicians and dermatologists is very low.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with hematologic malignancies, only higher level of immunosuppression was clearly associated with increased risk of HZ. In prior studies in the general population, factors associated with increased risk of HZ have included older age, disease, and drug-related suppression of cellular immunity, and to a lesser extent female gender (1,48,51). Data are more limited on the association between race/ethnicity and risk of HZ among otherwise healthy adults, with 2 studies finding that blacks were at lower risk than whites (5,52), and one study finding that HZ was less common among Hispanics than among non-Hispanic whites (53).…”
Section: Discussionmentioning
confidence: 99%
“…La carga de la enfermedad es semejante en todos los países desarrollados [4][5][6][7]38,133,137,138 .…”
Section: Carga De La Enfermedadunclassified